2022
DOI: 10.1111/ajt.17108
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CXCL9 and CXCL10 at allograft injury predict chronic lung allograft dysfunction

Abstract: Histopathologic lung allograft injuries are putative harbingers for chronic lung allograft dysfunction (CLAD). However, the mechanisms responsible are not well understood. CXCL9 and CXCL10 are potent chemoattractants of mononuclear cells and potential propagators of allograft injury. We hypothesized that these chemokines would be quantifiable in plasma, and would associate with subsequent CLAD development. In this prospective multicenter study, we evaluated 721 plasma samples for CXCL9/CXCL10 levels from 184 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…These findings call into question the characterization of ALI or OP as “non‐immune” patterns of injury in lung allograft recipients 12 . Supporting this idea, recent data indicate plasma and lung fluid levels of select chemokines, including CXCL9 and CXCL10, are elevated at the time of ALI in particular and that the prognostic implications of ALI on CLAD risk are dependent on the presence of chemokine activation 21 . Together these observations underscore that novel immunosuppression strategies that disrupt cellular or humoral immune activation are needed to mitigate the influence of these graft injury histologies on long‐term lung recipient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings call into question the characterization of ALI or OP as “non‐immune” patterns of injury in lung allograft recipients 12 . Supporting this idea, recent data indicate plasma and lung fluid levels of select chemokines, including CXCL9 and CXCL10, are elevated at the time of ALI in particular and that the prognostic implications of ALI on CLAD risk are dependent on the presence of chemokine activation 21 . Together these observations underscore that novel immunosuppression strategies that disrupt cellular or humoral immune activation are needed to mitigate the influence of these graft injury histologies on long‐term lung recipient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that mTORC2 orchestrates an upregulation of CXCR3 to curb hepatic fibrosis and enhances CXCR3/CXCL9 expression to alleviate dermal fibrosis (Richmond et al., 2023). Furthermore, there exists evidence underscoring the immunomodulatory effects of CXCR3/CXCL9 in fostering inflammation resolution and repair (Shino et al., 2022). Notably, the upregulation of CXCR3/CXCL9 has demonstrated an ability to impede activated collagen production in fibroblasts, thereby inhibiting the formation of fibrosis (Li et al., 2021).…”
Section: Dicussionmentioning
confidence: 99%
“…Biomarkers are emerging tools which may help identify which minimal rejection episodes may confer the greatest risk and warrant treating. One intriguing option is the chemoattractant CXCL9 which been shown to be elevated in BALF and serum in the setting of several underlying allograft injuries and predictive of future CLAD, though testing is not yet available in routine clinical practice and further study is needed [105,109,110].…”
Section: Approach To Minimal Armentioning
confidence: 99%